2014
DOI: 10.1111/avj.12247
|View full text |Cite
|
Sign up to set email alerts
|

Effective control of a suspected cyromazine‐resistant strain of Lucilia cuprina using commercial spray‐on formulations of cyromazine or dicyclanil

Abstract: Based on the results of these studies, there was no evidence of reduced susceptibility to cyromazine or dicyclanil and the periods of protection of sheep against L. cuprina were unaffected and consistent with the registered label claims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Currently, the prophylaxis against flystrike relies on synthetic insecticides, such as organophosphates and insect growth regulators (benzoylphenyl ureas, cyromazine and dicyclanil) [16; 17; 12] and, especially for Merino lambs in Australia's extensive wool industry, on painful surgical husbandry procedures such as the docking and the mulesing [18; 19]. However, the side effects of synthetic insecticides, such as the development of insect resistance [20], the harmful effects on sheep [21], farmers [22], and the environment [23], as well as the rising concerns about animal welfare [24] have made alternative strategies a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the prophylaxis against flystrike relies on synthetic insecticides, such as organophosphates and insect growth regulators (benzoylphenyl ureas, cyromazine and dicyclanil) [16; 17; 12] and, especially for Merino lambs in Australia's extensive wool industry, on painful surgical husbandry procedures such as the docking and the mulesing [18; 19]. However, the side effects of synthetic insecticides, such as the development of insect resistance [20], the harmful effects on sheep [21], farmers [22], and the environment [23], as well as the rising concerns about animal welfare [24] have made alternative strategies a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of blowfly infestations has traditionally relied on synthetic insecticides such as organochlorines, organophosphates and insect growth regulators [ 17 , 18 ]. However, the repeated insurgence of blowfly resistance to chemicals [ 19 ] and, the issues around the harmful effects of synthetic compounds on humans [ 20 , 21 ], animals [ 22 ] and the environment [ 23 ], have made new eco-friendly, low-cost tools a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…Cyromazine was used widely in the sheep industry for over 30 years before Levot 7 reported that larvae recovered from a property in southern NSW showed resistance to this compound, and to dicyclanil to a lesser extent, in in vitro assays. Baker et al 8 subsequently showed that thorough application of cyromazine-and dicyclanil-based products at the label's recommended doses resulted in effective control of blowflies on this property, for periods consistent with the registered label claims. This indicated that the low level of in vitro resistance was not impacting the period of protection if the chemical was applied correctly.…”
Section: Insecticidesmentioning
confidence: 88%